ANALISIS ANALISIS PRINSIP KESANTUNAN IMPERATIF DALAM TALKSHOW HOTROOM "MENAKAR KEADILAN DALA TUNTUTAN" - Dinda Tiara Wia Ningsih Dinda; Alber (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
Politeness is the ethics of communicating by using language as a medium of speech, which regulates polite language procedures. While the imperative is an utterance intending to order the interlocutor to do what the speaker wants. The method used in this research is descriptive method. This method applies the requirement that research must be based on existing facts so that the news or information provided is in accordance with the actual situation. The purpose of this study is to describe words that contain imperative meaning. The research subject is the Youtube Chanel, starring Hotman Paris with the theme of measuring justice in demands. The research object is imperative speech. The theory used to analyze imperative politeness is Chaer's theory. Data collection techniques use the YouTube video listening method. While the technique used is note-taking technique.